HIGH SCHOOL ENGLISH LANGUAGE TEACHER'S TEACHING STRATEGIES IN PROMOTING STUDENTS' VERBAL ENGAGEMENT IN ONLINE LEARNING - Dyandra Adelia Azzara, - (2022)
Student engagement has a significant role in achieving academic success. However, the sudden worldwide change forces students and teachers to shift to online learning, and it would lead to many difficulties shared by both teachers and students, effectively hampering students' motivation to actively engage in the classroom. This study is aimed to investigate a teacher's strategies in encouraging students' verbal engagement in the midst of online learning. This study employed a descriptive qualitative research design using discourse transcripts and teacher interview. The data collected through recordings and document analysis were analyzed qualitatively. The result of this study suggests that while problems and difficulties from online classes had proven to be quite difficult for the teacher to manage, but by making changes in her teaching strategy, she was able to improve the students' engagement in the lesson. The researcher recommends teachers to be resourceful in reaping benefits from having multiple teaching materials and alternating teaching techniques if faced with problems with retaining students' interest in the classroom.